2021
DOI: 10.1038/s41372-021-01086-7
|View full text |Cite
|
Sign up to set email alerts
|

Preventive bundle approach decreases the incidence of ventilator-associated pneumonia in newborn infants

Abstract: Objective We hypothesized that the implementation of evidence-based interventions shaping a bundle approach could significantly reduce the incidence of ventilator-associated pneumonia (VAP) in the neonatal intensive care unit. Study design We conducted a prospective observational cohort study including neonates undergoing mechanical ventilation >48 h. VAP rate and endotracheal intubation ratio were compared before (pre-period) and after (post-period) applying VAP prevention bundle strategies. Result One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In addition, neonates, who could exhibit distinct physiological responses to respiratory support, may notably benefit from optimized ventilator settings and tailored respiratory support post-reintubation, thereby reducing VAP incidence. 16,28 This unexpected observation prompts a re-evaluation of reintubation practices, particularly in neonatal care, and underscores the necessity for further investigative efforts.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, neonates, who could exhibit distinct physiological responses to respiratory support, may notably benefit from optimized ventilator settings and tailored respiratory support post-reintubation, thereby reducing VAP incidence. 16,28 This unexpected observation prompts a re-evaluation of reintubation practices, particularly in neonatal care, and underscores the necessity for further investigative efforts.…”
Section: Discussionmentioning
confidence: 96%
“…Incidence density in the VAP group was 10.86 per 1,000 ventilator-days in this study, similar to previous Spanish (10.9) and Iranian (11.6) studies, 6,17 but lower than earlier French (17.1) and Egyptian (29.2) studies 13,24 and higher than the INICC report (7.5, 95% CI: 6.9-8.1). 4 VAP prevention bundle strategies can reduce the incidence density of VAP (rates of pre-versus postperiod were 11.79 versus 1.93 in a study from Spain, 25 7.33 versus 2.71 in a study from Turkey, 26 and 36.4 versus 23.0 in a study Egypt 24 ). The VFDs of the VAP group (median ¼ 5, IQR: 0-16 days) in our study was lower than reported in a previous neonatal study (median ¼ 11, IQR: 5-17.7 days) 13 and adult study (average ¼ 11 [95% CI: 0-24]), 18 but the VFDs of the non-VAP group (median ¼ 24, IQR: 20-26 days) was similar to another study (median ¼ 22, IQR: 14-24 days).…”
Section: Discussionmentioning
confidence: 98%
“…Incidence density in the VAP group was 10.86 per 1,000 ventilator-days in this study, similar to previous Spanish (10.9) and Iranian (11.6) studies, 6 17 but lower than earlier French (17.1) and Egyptian (29.2) studies 13 24 and higher than the INICC report (7.5, 95% CI: 6.9–8.1). 4 VAP prevention bundle strategies can reduce the incidence density of VAP (rates of pre- versus postperiod were 11.79 versus 1.93 in a study from Spain, 25 7.33 versus 2.71 in a study from Turkey, 26 and 36.4 versus 23.0 in a study Egypt 24 ).…”
Section: Discussionmentioning
confidence: 98%
“…This explanation is confirmed by CDC, (2019) recommended that suctioning should be performed on an as needed basis after adequate evaluation of neonates, rather than a routine procedure to avoid complications such as hypoxemia and bradycardia. Similarly, Pinilla-González et al (2021) who reported that the suction procedure was accomplished according to the NICU protocol. Procedure should be performed by two nurses to ensure aseptic technique, only when ETT was obstructed and only when indispensable and using a dual suction system: one for the oral cavity and another for the airway both connected to a close-suction system.…”
Section: Discussionmentioning
confidence: 99%